Setting the international standard for longitudinal follow-up of patients with systemic sclerosis: a Delphi-based expert consensus on core clinical features - Yannick Allanore; Dinesh Khanna; Oliver Distler; Anna-Maria Hoffmann-Vold; Baron Murray; Otylia Kowal-Bielecka (RMD Open)
Background Systemic sclerosis (SSc) is a severe, progressive multiorgan disease but to date, there are no established standardised international guidelines for follow-up of patients with SSc. The goal of this project was to develop an expert consensus for annual systematic investigations in patients with SSc to enhance their standard-of-care.Material and methods The Delphi method was applied. All SSc experts from the European Scleroderma Trials and Research group network and the Scleroderma Clinical Trial Consortium were invited to participate. All experts were asked to answer questionnaires in five Delphi steps to determine the domains of interest and tools for each domain for an annual systematic assessment of patients with SSc. Each item was rated on a scale between 0% and 100% (not and very important), and parameters rated >80% by more than 75% of the experts were regarded as acceptable.Results In total, 157 experts worldwide participated with 71.3% experts seeing >50 patients with SSc annually. In the first round, 23 domains and 204 tools were suggested. After five Delphi steps, experts agreed on 10 domains including (1) Raynaud’s phenomenon; (2) Digital ulcers; (3) Skin and mucosa; (4) Lung; (5); Heart; (6) GI domain, (7) Renal; (8) Musculoskeletal; (9) Laboratory and (10) Treatment. Overall, 55 tools were identified including clinical assessments, laboratory measurements and imaging or functional investigations.Conclusion Through five Delphi steps with world leading experts, a consensus was established on strongly suggested tools for a minimum annual systemic assessment of organ involvement in SSc. This work should enhance the standardisation and homogenisation of the practices.